Democratization of Filling Regional Head Positions - Rogers, Maurice; Sagala, Christo Sumurung Tua; Munte, Herdi (Indonesian Journal of Law and Society, 2024)
The 2024 simultaneous regional head elections have significant implications for leadership vacancies across various regions. Consequently, to address these vacancies, interim regional heads will be appointed until definitive regional heads are elected following the 2024 elections. This paper aims to scrutinize the representation of the populace within the framework of appointing regional heads in Indonesia and to evaluate the concept of democratization as an ideal approach for selecting acting officer of regional heads. Through a normative analysis of diverse sources and prevalent social phenomena, it is asserted that democratization in the process of appointing regional heads is imperative for fostering leaders' accountability to their constituents. However, the current practice of appointing regional heads in Indonesia often diverges from democratic principles. Central government retains exclusive authority to appoint acting officer of regional heads through a closed, non-transparent process devoid of public participation. This process risks signaling vested interests between the appointing authority and the recipients of office. Therefore, reforming the system for appointing acting officer of regional heads becomes imperative to facilitate public involvement directly or through parliamentary institutions. This involvement should span the proposal, discussion, determination, monitoring, evaluation, and dismissal stages of acting regional heads. Furthermore, candidates for these positions should be limited based on the principle of regional autonomy. This entails requiring candidates to originate from the state civil apparatus as administrative officials or civil servants with extensive experience in the relevant region. Such requirements ensure that candidates possess a comprehensive understanding of governmental managerial duties, public service obligations, and the specific conditions and needs of the region and its populace. Keywords: Regional Head Vacancy, Representation of the People, Acting Officier of Regional Head, Simultaneous Regional Head Election 2024